Living with HIV and ARVs - Squire, C. author. aut Link
VI, 275 p.
Keywords: This book explores the possibilities and difficulties of living with HIV and ARVs, or antiretroviral treatment, today. It draws on HIV-positive people's stories from both the UK and the South African epidemics and offers a deep understanding of the continuing difficulties of living with HIV and the effective strategies for coping that have evolved.